Biomass production in wheat in relation to evaporative demand and ambient temperature - CHAKRAVARTY, N. V. K.; SASTRY, P. S. N. (MAUSAM, 1983)
Biomass production in 3 varieties of wheat grown under irrigated field conditions was found to be linearly related to cumulative evaporation and accumulated heat units above certain threshold value. Biomass production estimates at different levels of cumulative evaporation and accumulated heat indicated the possibility of using this information for a qualitative assessment of varietal response to evaporative demand and thermal regime prevailing in the region.